Pengaruh Struktur Modal, Kebijakan Deviden dan Liuiditas Terhadap Harga Saham Dimoderasi oleh Ukuran Perusahaan - Kevin Apri Wicaksono; Dwi Ermayanti Susilo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study investigates the impact of capital structure, dividend policy, and liquidity on stock prices, with company size functioning as a moderating variable for companies listed on the Indonesia Stock Exchange.The research method used is descriptive with a quantitative approach. Data collection was conducted using purposive sampling with data from 10 companies that consistently appeared on the IDX 30 list during the research period. Based on the research results, it can be concluded that capital structure, dividend policy, and liquidity have a significan